2017
DOI: 10.21276/ijee.2017.10.0239
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Water Quality: A Case Study of River Yamuna

Abstract: 81-8.00, 1046.5-1195.3 µS/cm, 27.0-37.3 NTU, 856.5-936.0 mg/l, 4.5-5.2 mg/l, 19.3-25.8 mg/l, 58.0-85.0 mg/l, 242.5-267.0 mg/l and 97.75-114.0 mg/l respectively. The results on the water quality parameters of Yamuna river indicate that the river is not safe for domestic purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Lower values of sulfate (7.0-16.5 mg/l) were obtained while assessing the water quality parameters of Markanda river, India [18]. However comparatively higher values of SO4 2-(97.75-114.0 mg/l) were observed for Yamuna river at Yamunanagar region of Haryana, India and were found below the prescribe limits of BIS [25]. Statistical analysis for SO4 2-is presented in Table III.…”
Section: F Sulfate (So4 2-)mentioning
confidence: 99%
See 1 more Smart Citation
“…Lower values of sulfate (7.0-16.5 mg/l) were obtained while assessing the water quality parameters of Markanda river, India [18]. However comparatively higher values of SO4 2-(97.75-114.0 mg/l) were observed for Yamuna river at Yamunanagar region of Haryana, India and were found below the prescribe limits of BIS [25]. Statistical analysis for SO4 2-is presented in Table III.…”
Section: F Sulfate (So4 2-)mentioning
confidence: 99%
“…Water samples collected from river Markanda and correlation matrix was used to know the relationship between water quality parameters [18,29]. Correlation matrix was prepared between eight different water quality parameters and is presented in Table V.…”
Section: K Correlation Matrix Analysismentioning
confidence: 99%
“…The groundwater quality studies reveals that water is suitable for drinking, agricultural and industrial purposes if certain water quality/computed parameters found within the desired limits. Many studies on quality of ground and surface water sources on [18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. Although many studies have been conducted on suitability of groundwater for domestic needs, however, no extensive study has been done on suitability of water for irrigation purposes with respect to residual sodium carbonate (RSC) in Solan district of the hilly state Himachal Pradesh.…”
Section: Introductionmentioning
confidence: 99%
“…All living things on our planet need water for their survival and development 1 . Water has ability to dissolve organic as well as inorganic compounds in it; hence water is called as universal solvent [3][4] . Water is used for various purposes like drinking, irrigation, transportation, washing, mass bathing and waste disposal for industries 5 .…”
Section: Introductionmentioning
confidence: 99%